Novel mouse models of oculopharyngeal muscular dystrophy (OPMD) reveal early onset mitochondrial defects and suggest loss of PABPN1 may contribute to pathology. (29th May 2017) - Vest, Katherine E.; Phillips, Brittany L.; Banerjee, Ayan; Apponi, Luciano H.; Dammer, Eric B.; Xu, Weiting; Zheng, Dinghai; Yu, Julia; Tian, Bin; Pavlath, Grace K.; Corbett, Anita H.
Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a late onset disease caused by polyalanine expansion in the poly(A) binding protein nuclear 1 (PABPN1). Several mouse models have been generated to study OPMD; however, most of these models have employed transgenic overexpression of alanine-expanded PABPN1. These models do not recapitulate the OPMD patient genotype and PABPN1 overexpression could confound molecular phenotypes. We have developed a knock-in mouse model of OPMD ( Pabpn1 +/A17 ) that contains one alanine-expanded Pabpn1 allele under the control of the native promoter and one wild-type Pabpn1 allele. This mouse is the closest available genocopy of OPMD patients. We show that Pabpn1 +/A17 mice have a mild myopathic phenotype in adult and aged animals. We examined early molecular and biochemical phenotypes associated with expressing native levels of A17-PABPN1 and detected shorter poly(A) tails, modest changes in poly(A) signal (PAS) usage, and evidence of mitochondrial damage in these mice. Recent studies have suggested that a loss of PABPN1 function could contribute to muscle pathology in OPMD. To investigate a loss of function model of pathology, we generated a heterozygous Pabpn1 knock-out mouse model ( Pabpn1 +/Δ ). Like the Pabpn1 +/A17 mice, Pabpn1 +/Δ mice have mild histologic defects, shorter poly(A) tails, and evidence of mitochondrial damage. However, the phenotypes detected in Pabpn1 +/Δ mice only partially overlap with those detected in Pabpn1 +/A17 mice. These results suggest that loss of PABPN1 function could contribute to but may not completely explain the pathology detected in Pabpn1 +/A17 mice.